Tales from the global economy Santa : supply and demand - Newson, Jeremy; British Broadcasting Corporation ([S.l.] : BBC Active, 2006)
In the industrialized world, Christmas means megabucks to the businesses that can create a fad or spot a trend. Filmed from a U.K. perspective ... The dynamics of--and glitches in--the global supply and demand cycle are thoroughly covered, factoring in the effects of brands, product licensing, advertising, research and development, and offshore manufacturing
Title from title screen
Executive producer, Gina Newson ; editor, Jason Sawage ; sound, Muray Clark...[et al.] ; camera, Phil Broom...[et al.]
Keywords: Christmas -- Economic aspects -- Great Britain; Christmas -- Economic aspects; Consumption (Economics)